Kincsek az egyetemen: A titokzatos festmény - Béres, Zsuzsa (Gerundium, 2018)
Treasures at the University – The mysterious Painting. For decades the Rectorial Council Hall of the Main Building of the University of Debrecen has been decorated by a large-sized painting created by Iványi- Grünwald Béla, that is titled: Dull Mihály elítélése [that translates as: Sentencing of Mihály Dull]. Until now, however, hardly just legends have been circling around about how, when and under what circumstances the painting was brought to Debrecen. The author of the writing attempts to explore the reality behind these legends.